Pengaruh Modifikasi Aktivitas Pemanasan Khusus Pembelajaran Sepak Bola Terhadap Motivasi Belajar Siswa Kelas VIII - Muhammad Rizky Auliya Pratama; Moh. Fathur Rohman (JURNAL ILMIAH NUSANTARA, 2026)
This study was motivated by the low level of students’ learning motivation in Physical Education, particularly in soccer learning. One effort to improve students’ learning motivation is by providing engaging learning activities, one of which is through the modification of warm-up activities. This study aims to determine the effect of modified warm-up activities in soccer learning on the learning motivation of eighth-grade students at SMP Negeri 46 Surabaya. This research employed a quantitative method with a quasi-experimental design. The sample consisted of 33 eighth-grade students. The research instrument used was a student learning motivation questionnaire. Data analysis techniques included descriptive statistics, normality testing, and hypothesis testing using the paired sample t-test with the assistance of SPSS software. The results showed that the average score of students’ learning motivation increased from 60.48 in the pretest to 82.21 in the posttest. The normality test indicated that the data were normally distributed. Furthermore, the hypothesis test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest scores. In addition, the effectiveness test using the N-Gain Score showed an average value of 0.59, which falls into the moderate effectiveness category. Based on these findings, it can be concluded that the modification of warm-up activities in soccer learning has a significant effect on improving the learning motivation of eighth-grade students at SMP Negeri 46 Surabaya.